Opioid pain medication prescription for chronic pain in primary care centers: the roles of pain acceptance, pain intensity, depressive symptoms, pain catastrophizing, sex, and age - Ramírez-Maestre, C.; Reyes-Pérez, Á.; Esteve, R.; López-Martínez, A. E.; Bernardes, S.; Jensen, M. P. (International Journal of Environmental Research and Public Health, 2020)
Background: Psychological factors of patients may influence physicians’ decisions on prescribing opioid analgesics. However, few studies have sought to identify these factors. The present study had a double objective: (1) To identify the individual factors that differentiate patients who had been prescribed opioids for the management of chronic back pain from those who had not been prescribed opioids and (2) to determine which factors make significant and independent contributions to the prediction of opioid prescribing. Methods: A total of 675 patients from four primary care centers were included in the sample. Variables included sex, age, pain intensity, depressive symptoms, pain catastrophizing, and pain acceptance. Results: Although no differences were found between men and women, participants with chronic noncancer pain who were prescribed opioids were older, reported higher levels of pain intensity and depressive symptoms, and reported lower levels of pain-acceptance. An independent association was found between pain intensity and depressive symptoms and opioid prescribing. Conclusions: The findings suggest that patient factors influence physicians’ decisions on prescribing opioids. It may be useful for primary care physicians to be aware of the potential of these factors to bias their treatment decisions.